OPPORTUNITIES FOR RESEACH IN HELMINTHOLOGY IN PERU: MY OWN EXPERIENCE - Wetze, Eric (2009)
As a professor of Parasitology and Invertebrate Biology at a small, private liberal arts college in the United States, where I study the transmission ecology of trematode parasites, to date my research experience studying helminths in the Neotropical region has been limited. Of course, many parasitologists in North America and elsewhere have relatively limited exposure to neotropical helminthology beyond textbooks and the primary literature; however, based on my own experience over the last year I believe there exists great opportunity for this to change. The potential for wonderful and productive collaborations continues to increase with greater ease of travel and levels of cooperation and information-sharing. So, while by definition my own experience in Peru is unique to me, I hope that it highlights some of the opportunities for research in helminthology in Peru and thus encourages additional collaborations in the future.